2022
DOI: 10.3389/fonc.2022.931050
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic Stem Cell: A Mini-Review on Clinical Perspectives

Abstract: Hematopoietic stem cells (HSCs) are known for their ability to proliferate and self-renew, thus being responsible for sustaining the hematopoietic system and residing in the bone marrow (BM). Leukemic stem cells (LSCs) are recognized by their stemness features such as drug resistance, self-renewal, and undifferentiated state. LSCs are also present in BM, being found in only 0.1%, approximately. This makes their identification and even their differentiation difficult since, despite the mutations, they are cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…A major challenge in the treatment of acute myeloid leukemia is the survival of a few therapy-resistant cells. These cells, known as leukemia stem or initiating cells (LSCs or LICs), which are one of the the key factors contributing to disease progression and relapse 31,48,52,53 . To show the potential of the Cell Marker Accordion in identifying disease-critical cells in human blood cancers, we analyzed a published scRNA-seq dataset of CD34+ bone marrow cells from 5 healthy controls and 14 acute myeloid leukemia patients 54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge in the treatment of acute myeloid leukemia is the survival of a few therapy-resistant cells. These cells, known as leukemia stem or initiating cells (LSCs or LICs), which are one of the the key factors contributing to disease progression and relapse 31,48,52,53 . To show the potential of the Cell Marker Accordion in identifying disease-critical cells in human blood cancers, we analyzed a published scRNA-seq dataset of CD34+ bone marrow cells from 5 healthy controls and 14 acute myeloid leukemia patients 54 .…”
Section: Resultsmentioning
confidence: 99%
“…To fill this gap, the Cell Marker Accordion includes weighted collections of marker genes associated with disease-critical cells in the most common blood cancer types, mostly linked to acute myeloid leukemia (AML), multiple myeloma (MM) and lymphoma. In AML and MM patients, the persistence of therapy-resistant leukemia stem cells and malignant plasma cells respectively, inevitably increases the risk of relapse and reduces overall treatment effectiveness 31,48,52,53 . By exploiting scRNA-seq datasets from AML and MM patients, we showed that the Cell Marker Accordion effectively identifies aberrant cell types and extracts altered gene signatures.…”
Section: Discussionmentioning
confidence: 99%
“…To understand this relationship between cancer progression and CSCs, we should first recognise the nature of CSCs. Thus, the most relevant differentiating and characterising features of normal stem cells and CSCs are included in Table 1 [2][3][4]6,9,10,13,[23][24][25][26][27][28][29][30]. Notch, Oct4, Sox1: specific genes for all stem cells; ALDH1: aldehyde dehydrogenase 1; CD24: a small surface protein responsible for cell-extracellular matrix (ECM) and cell-cell interactions; CD34: a transmembrane glycoprotein expressed on early lymphohematopoietic stem cells, progenitor cells, and endothelial cells; CD44: a multifunctional glycoprotein responsible for cell adhesion, signalling, proliferation, migration, haematopoiesis, and lymphocyte activation; CD90: a glycophosphatidylinositol (GPI) anchored conserved cell surface protein; CD133: also known as prominin-1, a transmembrane cell surface glycoprotein commonly utilised as a hematopoietic stem cell marker; CSCs: cancer stem cells; DNA: deoxyribonucleic acid; EpCAM: epithelial cell adhesion molecule; ESA: epithelial-specific antigen; IL-4: interleukin 4; * It means that Early-stage CSCs and Late-stage CSCs are subpopulations of CSCs.…”
Section: Cancer Stem Cells: Origin and Detailed Characteristicsmentioning
confidence: 99%
“…From the phenotypic alterations that occur in a neoplastic clone, the surface antigens also undergo changes that can be used to identify and characterize these cells. Due to the variability of immunophenotypic changes present in leukemic cells, they can be categorized into groups: expression of crossline antigens, asynchronous expression of maturational markers, expression of decreased or absent antigens, and overexpression of antigens [ 21 , 55 , 56 ].…”
Section: Immunophenotyping In Acute Myeloid Leukemia Cellsmentioning
confidence: 99%
“…Alterations in DNMT3A were present in patients in five different studies described in Table 1 , and they are also common mutations in early leukemic stages that confer proliferative advantages to pre-leukemic cells [ 56 ]. DNMT3A activity on gene methylation directly influences AML development, as either hypermethylation of tumor suppressors or hypomethylation of oncogenes might act as drivers of leukemogenesis onset [ 90 ].…”
Section: Immunophenotyping X Genetics In Amlmentioning
confidence: 99%